Design and Development of the Interactive Courseware Called Various of Organizing Student Activities (VOSA), Based on SCORM - Dea Komalasari, Mahilda; Sukadari, S; Widyaningsih, Nina (KnE Social Sciences, 2022)
This research analyzed the flaws in today’s educational media system by examining the development of interactive courseware for distance learning called Various of Organizing Student Activities (VOSA), based on SCORM. The development, system structure, elements and advantages of the VOSA interactive courseware were investigated and described. VOSA is reusable, portable, renewable, and simple to use. It could be used to develop an online distance learning system. Furthermore, it has the potential to improve the efficiency and quality of learning media in learning practices, independent learning, examinations, and evaluations. Keywords: interactive courseware, VOSA, SCORM, distance learning system